Research on the Preparation of C4 Olefins by Ethanol Coupling Based on Regression Analysis and Optimized Model - Jingjing Wu, Xiaoya Yang (Forest Chemicals Review)
As a green raw material to prepare C4 olefins, ethanol molecules have wide sources, clean and low in consumption with considerable economic and environmental benefits. For the sake of improving the yield of C4 olefins by changing catalyst combinations in ethanol coupling, several sets of controlled experiments under different catalyst and temperature conditions were designed in this paper to search the effect of different catalyst combinations and temperatures on the conversion rate of ethanol and the selection of C4 olefins. And based on regression analysis, we established the yield of C4 olefins about independent variables including the catalyst carrier, Co loading, total Co/SiO2, Co/SiO2 and HAP loading ratio, ethanol concentration and temperature, in accordance with experimental data. Then we optimized the model to further explore ways to increase C4 olefin production. In this study, selecting the appropriate catalyst combination is helpful to realize the stable and efficient production of C4 olefins.